ANALISIS KAPASITAS SUMBER DAYA MANUSIA PETANI HIDROPONIK DI KOTA KENDARI - Salahuddin, Salahuddin; Malik, Nurhayu (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
The objective of this study is to analyze the capacity of farmers' resources in managing hydroponic farming in Kendari City. The population of this study consists of all hydroponic farmers in Kendari City, with a total sample size of 30 individuals, who were selected using a census method. The data analysis in this study utilizes descriptive statistics. Descriptive statistics are employed to delineate and characterize the state of the research variables. The results of the study indicate that the capacity of hydroponic farmers in Kendari City is in the moderate category. Hydroponic farmers in Kendari possess the necessary managerial, technical, and social competencies to effectively manage and develop hydroponic farming. The managerial and technical capacities of hydroponic farmers in Kendari City are categorized as moderate. The social capacity of hydroponic farmers in Kendari City is categorized as high.